PERUBAHAN POLA KOMUNIKASI DALAM MASYARAKAT AKIBAT PENGGUNAAN APLIKASI PESAN INSTAN - Gunawan Widjaja (Prosiding Seminar Nasional Indonesia, 2025)
The use of instant messaging applications has led to significant changes in people's communication patterns. The resulting positive impacts include increased efficiency, speed and expansion of social connectedness. These apps facilitate faster and more responsive communication with additional features such as video and voice calls, and enable the formation of more diverse virtual communities and discussion groups. However, there are also emerging challenges, such as the risk of misunderstandings, technology dependency, and a decline in the quality of face-to-face interactions. In addition, the rapid spread of information through these applications may increase the risk of disinformation. Therefore, it is important for people to improve their digital literacy and use instant messaging technology wisely to maximise the benefits while minimising the negative impacts.